2022
DOI: 10.1097/tp.0000000000004353
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting Kidneys From Donors With SARS-CoV-2 RNA Positivity in Brazil: Early Success Under a Detailed Surveillance Approach

Abstract: Viana et al any case of donor-derived SARS-CoV-2 infection in recipients of positive deceased-donors under the current Brazilian Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…This protocol included reverse transcription polymerase chain reaction testing on nasal and oropharyngeal swabs, blood, and urine on days 7, 14, 21, and 28 posttransplantation, effectively confirming the absence of any donor-derived infections. 15 This approach yielded crucial insights for the Brazilian healthcare authorities, supporting the safety of the utilization of organs from SARS-CoV-2–positive donors.…”
Section: Outcome Of Our Strategic Approachmentioning
confidence: 96%
“…This protocol included reverse transcription polymerase chain reaction testing on nasal and oropharyngeal swabs, blood, and urine on days 7, 14, 21, and 28 posttransplantation, effectively confirming the absence of any donor-derived infections. 15 This approach yielded crucial insights for the Brazilian healthcare authorities, supporting the safety of the utilization of organs from SARS-CoV-2–positive donors.…”
Section: Outcome Of Our Strategic Approachmentioning
confidence: 96%
“…A atividade de transplante aumentou progressivamente com a ampla disponibilidade de testes, maior conhecimento da doença e das opções de tratamento, disponibilidade de vacinas e a redução observada nas taxas de letalidade em grupos de alto risco, incluindo idosos, pacientes com doença renal crônica e receptores de transplante renal, mitigando ainda mais a sobrecarga para as unidades de diálise. Após a observação de que o SARS-CoV-2 não podia ser transmitido através de órgãos sólidos, com exceção os pulmões, a maioria dos centros começou a realizar transplantes utilizando órgãos de indivíduos com testes positivos para SARS-CoV-2 que haviam falecido por outras causas 7 .…”
Section: Transplantar Ou Não Transplantar Durante Uma Pandemia?unclassified
“…In addition to the reported safety of transplanting kidneys from donors with COVID-19, case reports and series have provided some evidence for good short-term recipient outcomes. [11][12][13][14][15][16] Moreover, largescale studies using the US Organ Procurement and Transplantation Network database have revealed graft and patient survival of recipients of kidneys from SARS-CoV-2 RNA-positive donors that were comparable with those from SARS-CoV-2 RNA-negative donors. [4][5][6]22 However, a more recent singlecenter retrospective study revealed acceptable but worse short-term graft function for recipients of kidneys from SARS-CoV-2 RNA-positive donors with COVID-19-related cause of death compared with those from SARS-CoV-2 RNA-negative donors.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Clinical practice in many centers soon evolved toward transplanting kidneys from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RNA-positive donors and from those who died of COVID-19. [11][12][13][14][15][16][17] To date, despite evidence suggesting that SARS-CoV-2 infects not only the lung but also extrapulmonary organs, [18][19][20][21] no COVID-19 transmission has been reported from infected donors to negative recipients of non-lung solid-organ transplants.…”
Section: Introductionmentioning
confidence: 99%